A study on problem diagnosis and maintenance guideline of small scale PV system - Chul Kim, Hee (International Journal of Engineering and Technology, 2018)
Background/Objectives: Research and development of low-cost, high-efficiency devices that can be installed without replacing existing power generation equipment is promoted early. It is aimed to prevent the damage of property and human life by detecting the fire of PV system. Therefore, it is possible to easily install the device without replacing the solar module The aim is to minimize the damage to people.Methods/Statistical analysis: In order to prepare for the safety accidents of the photovoltaic power generation facilities due to fire and blast, the monitoring system should have the following functions as essential. Measures and analyzes the voltage and current of power generated in each string in the connection board in real time. An alarm is triggered when an abnormality of a specific string is detected or when an abnormal temperature change is detected in the connection panel internal temperature sensor.If the smoke sensor inside the connection panel detects smoke generation and an abnormality such as a fire is caught, the monitoring system immediately generates an alarm.Findings: It provides services such as checking the status of customer power plants, improving power generation efficiency, and recovering quickly in case of a disaster through a monitoring system that supports stable operation of the PV plant and profit generation. By using the existing connection box function as it is, the company minimized the additional cost, and promoted and promoted a low-cost, high-efficiency system.Improvements/Applications: H/W module using temperature and smoke sensor is interlocked with existing connection semi-control system to develop efficient connection monitoring device. In order to link the sensor value with the monitoring system, messages are added and supplemented. For the application of the fail-safe solution, we developed a monitoring device to prevent the escape of the solar module and developed the H / W module using the vibration and loosening sensor. We will develop the solar monitoring system based on cloud type IoT platform by linking the fault recognition and alarm generation function by adding / supplementing the sensor value to link with the monitoring system.As a power station management for cloud type (ASP) service, adoption of oneM2M standard based IoT platform can expand acceptance by monitoring web and mobile based monitoring as well as real time monitoring and fault monitoring of solar power plant.Â Â